Chromatin‐level regulation of the fragmented dothistromin gene cluster in the forest pathogen Dothistroma septosporum. Issue 4 (5th January 2018) - Chettri, Pranav; Dupont, Pierre‐Yves; Bradshaw, Rosie E.
Summary: Genes required for fungal secondary metabolite production are usually clustered, co‐regulated and expressed in stationary growth phase. Chromatin modification has an important role in co‐regulation of secondary metabolite genes. The virulence factor dothistromin, a relative of aflatoxin, provided a unique opportunity to study chromatin level regulation in a highly fragmented gene cluster that is switched on during early exponential growth phase. We analysed three histone modification marks by ChIP‐qPCR and gene deletion in the pine pathogen Dothistroma septosporum to determine their effects on dothistromin gene expression across a time course and at different loci of the dispersed gene cluster. Changes in gene expression and dothistromin production were associated with changes in histone marks, with higher acetylation (H3K9ac) and lower methylation (H3K9me3, H3K27me3) during early exponential phase at the onset of dothistromin production. But while H3K27me3 directly influenced dothistromin genes dispersed across chromosome 12, effects of H3K9 acetylation and methylation were orchestrated mainly through a centrally located pathway regulator gene DsAflR . These results revealed that secondary metabolite production can be controlled at the chromatin‐level despite the genes being dispersed. They also suggest that patterns of chromatin modification are important in adaptation of a virulence factor for a specific role in planta . Abstract : Some fungi make secondary metabolites to help cause disease in plants. One secondary metabolite is dothistromin, a toxin made by a fungal pine pathogen. We show how a dispersed set of genes required for dothistromin production is co‐regulated by modification of proteins that determine whether the genes are tightly or loosely packed in the DNA.